A Causal Model of Factors Influencing Compliance of Corporate Income Tax Law of Small and Medium Enterprises (SMEs) in the Northeast of Thailand - Jatuchai, Surisa; Pitiphat, Supagrit (Modern Management Frontier Journal, 2024)
This research aimed to examine the effect of perceived tax fairness, moral of taxpayer, and tax knowledge on the compliance of corporate income tax law. A sample of 421 small and medium enterprises (SMEs) in the northeast of Thailand were selected by simple random sampling. Data were analyzed by confirmatory factor analysis, and path analysis. The results revealed that the model fits with the empirical data. Factor that has the most positive effect on the compliance of corporate income tax law is moral of taxpayer factor. Tax knowledge factor and perceived tax fairness factor also have positive effect on the compliance of corporate income tax law consequently. In addition, factors in the model can explain variance on the compliance of corporate income tax law by 65%.